Participation of Judicial Decisions as The Form of The Implementation of Moral Values in Case Statement Based on Rechtvinding Activities and Negative Wetjlike Theorie - Ikhda Zikra; Cuong Lan Minh (Contemporary Issues on Interfaith Law and Society, 2022)
The judge is the spearhead as well as the parameter of justice test conducted by the justice seekers. One of them through decisions issued by the judge, many things that need to be considered and considered by the judge in deciding a case, especially because the justice is universal and the science of law which is a science that is multidisciplinary means not monotonous or only limited to eyeglasses or juridical point of view only but need to pay attention to other values ​​that live, grow, and develop in society both written and written. Article 16 and 28 of Law Number 4 Year 2004 as already amended into Law mandates that judges are prohibited from refusing cases that enter the Court under the pretext that the law does not regulate, it is unclear but is obliged to examine and decide upon the case. Then in article 28 explained that the judge must dig the values ​​that exist in society. This is to ensure a sense of justice for the community because the law is not what is contained in the law alone but also pay attention to other laws that are Living Law and Unwritten Law in the form of habits that exist in society, customs, or traditions is still acknowledged and lives, grows, and develops with the community based on the mandate of Pancasila and the Constitution of the Republic of Indonesia which is accommodated in Article 18 B Paragraph (2) that "the state recognizes and respects the unity of society as long as it exists within the community" in its legal considerations shall explore and include these values ​​for the implementation of social justice for all Indonesian people. So, the judge's conviction in deciding a case also greatly affects the content of the decision so as not to negate the existing morality as a unity of values ​​that live and grow in society. HLA Hart acknowledges that law and morals have a very close relationship, even Hart reveals that between law, justice and morality has a very close relationship, even one of the aspects of justice, namely administrative justice, in the law of the minimum nature of law and morality.